Social and personal factors of stable remission for people with drug addictions. - Petrova, H. A.; Zavarzina, O. O.; Kytianova, I. P.; Kozyakov, R. V. (Psychology in Russia: State of Art, 2015)
This article presents research on the most effective measures in rehabilitation programs for people with chemical addictions and research on the personal characteristics that influence the complete cessation of drug and alcohol consumption. Building a model of an effective rehabilitation process is one of the most significant problems in organizing aid for drug and alcohol addicts. Analysis of the results of previous research revealed a number of factors that influence the stability of remission: individual biological factors (general state of health, presence of co-existing diseases); individual psychological factors (coping strategies, shifting of attention, self-control, aggressiveness); rehabilitation program factors (duration of programs, rehabilitation measures, form of rehabilitation, conditions for admission to a rehabilitation center); social factors (family support, rehabilitation with children, availability of communities with no drug addictions); spiritual factors (call to a divine power for help). We have researched the most effective measures of rehabilitation programs for people with chemical addictions, as well as personal characteristics that influence the full cease in drug and alcohol consumption.